PRINSIP, KETENTUAN, DAN KARAKTERISTIK PEMBIAYAAN (BANK) SYARIAH - Hendy Herijanto (ISLAMINOMICS: JOURNAL OF ISLAMIC ECONOMICS, BUSINESS AND FINANCE, 2014)
The characteristics of Islamic financing must follow the governingQur’anic verses and the Hadis of the Prophet Muhammad Puh. Thismeans that the epistemology derives from the Tauhidi Principle,being different from the one of the conventional economy andbanking that is deriving from the western culture and purely rationalthinking. Their basic and main principles are for the creation ofboth, the individual and collective well being of the society,consisting of Tauhidi Principle, vicegerency, justice, and materialand spiritual balances. These principles can be fulfilled by adheringto the Qur’anic stipulations, ie, emphasizing on trade and doing noribawi transactions (QS. 2: 275), and working on cooperative basis(QS. 5: 2). These stipulations bring about a deep and widesignificance and implication.For creating the collective well being of the society, Islamicfinancing can only be implemented by using the existing contracts,without riba, non gharar, non maysir, aiming on non ribawi workresults, common profit, using quasi equity and not purely moneyloan, risk sharing concept, being trustworthy, and keeping promisesreligiously. Consequently, money is put in its basic function that isas a medium of exchange and as a measure of the counter valuebeing goods, services, and productive business in the real sector ofthe economy.